Serosurvey in Two Dengue Hyperendemic Areas of Costa Rica Evidence Active Circulation of WNV and SLEV in Peri-Domestic and Domestic Animals and in Humans - Marta Piche-Ovares; Mario Romero-Vega; Diana Vargas-González; Daniel Felipe Barrantes Murillo; Claudio Soto-Garita; Jennifer Francisco-Llamas; Alejandro Alfaro-Alarcón; Carlos Jiménez; Eugenia Corrales-Aguilar (Pathogens, 2022)
Costa Rica harbors several flaviviruses, including Dengue (DENV), Zika (ZIKV), West Nile virus (WNV), and Saint Louis encephalitis virus (SLEV). While DENV and ZIKV are hyperendemic, previous research indicates restricted circulation of SLEV and WNV in animals. SLEV and WNV seroprevalence and high transmission areas have not yet been measured. To determine the extents of putative WNV and SLEV circulation, we sampled peri-domestic and domestic animals, humans, and mosquitoes in rural households located in two DENV and ZIKV hyperendemic regions during the rainy and dry seasons of 2017–2018 and conducted plaque reduction neutralization test assay for serology (PRNT) and RT-PCR for virus detection. In Cuajiniquil, serological evidence of WNV and SLEV was found in equines, humans, chickens, and wild birds. Additionally, five seroconversion events were recorded for WNV (2 equines), SLEV (1 human), and DENV-1 (2 humans). In Talamanca, WNV was not found, but serological evidence of SLEV circulation was recorded in equines, humans, and wild birds. Even though no active viral infection was detected, the seroconversion events recorded here indicate recent circulation of SLEV and WNV in these two regions. This study thus provides clear-cut evidence for WNV and SLEV presence in these areas, and therefore, they should be considered in arboviruses differential diagnostics and future infection prevention campaigns.